A Comparative Analysis of Buzzer and Non-Buzzer Comment on Prabowo’s Instagram Posts - Sinaga, Tantiara Fiesta; Beru Sembiring, Inggrid Gavrila; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This study examines the stylistic differences between buzzer and non-buzzer hate comments on Prabowo’s Instagram posts during the 2024 Indonesian presidential election campaign. The objective is to identify distinct linguistic features used by buzzers and ordinary users in expressing hate or criticism. This qualitative descriptive research applies Searle’s Speech Act Theory and a comparative stylistic analysis. Data were collected from Instagram using manual classification and analyzed based on five speech act categories. The findings show that buzzer comments are typically short, slogan-like, emotionally charged, and repetitive, dominated by assertive speech acts. In contrast, non-buzzer comments are more varied in tone and form, reflecting personal opinion, satire, and critical reflection. This study concludes that buzzer discourse tends to serve persuasive and propagandistic purposes, while non-buzzer discourse reflects more authentic and individual political expression.